Experimental Studies on Flow Structures Behind Bluff Bodies and Suppression of Vortex Street - Teimourian, Amir (Eastern Mediterranean University EMU, 2016)
One of the most significant features of flow around bluff bodies is the formation of vortices in the downstream wake. Such unsteady wake could incur unsteady loading where the vortex-induced vibration can have destructive effects on the structure of sky scrapers, cooling towers, chimneys and bridges which civilization relies on. In this study vortex shedding in the wake region of single and dual bluff bodies have been investigated, and possible passive flow control method have been employed to suppress formation of vortex street in the wake region downstream the bluff bodies. In this study the effects of entrainment of fluid through perforated surface on suppression of vortex street behind Perforated Square Cylinder have been studied experimentally. Wake region have been investigated in terms of coherent flow structure, time averaged properties and effectiveness of different perforations. The quantitative measurements revealed that the perforated surfaces are only effective within width interval of y/D= ±1.0. It was observed that in the near wake region up to approximately 1.5D downstream the wake, the shedding phenomenon has been suppressed significantly. It was also demonstrated that velocity profiles and flow structure affected by different perforated surfaces, and as a result coherent structures have been diminished considerably. In addition, interacting wakes of two inclined flat plates in tandem arrangement have been studied experimentally. The effects of gap ratio (g/D) between the plates together with angle of attack (α) on the flow structure in the wake region, incoherent and coherent time averaged properties profiles have been investigated. Different set of experiments have been conducted for gap ratios 0.5 and 1.5 between the plates, replicating single and dual body vortex shedding mode. In addition, various angle of iv attack (45-75 degree) have been studied to probe the effects of inclination on the wake region in terms of shedding frequency and Strouhal number variation. The results revealed that Strouhal number decreases as angle of attack increases. Moreover, increasing gap ratio affects the flow structure and as gap ratio increases, incoherent Turbulent Kinetic Energy production in the downstream wake have been decreased. Keywords: Vortex Shedding, Suppression, incoherent and coherent flow structure, Perforated Square Cylinder, Inclined flat plate, Interacting wake, Tandem arrangement

ÖZ: Cisimlerin etrafındaki akışların en belirgin özelliklerinden biri da cismin gerisinde oluşan girdaplardır. Böyle düzensiz dalgalı titreşimlere neden olarak yüksek yapılarda, bacalarda, soğutma kulelerinde ve köprülerde düzensiz yüklemelere ve yıkıcı etkilere sebep olabilmektedir. Bu çalışmada tek ve çift cisimlerin arkalarında oluşan dalgalardaki girdaplar araştırılmış ve pasif control metodları uygulanarak girdap oluşumunun engellenmesi araştırılmıştır. Bu çalışmada ayrıca delikli kare silindir üzerine akışın dolması ve arkasındaki girdap oluşumu incelenmiştir. Dalga alanı koherent akış yapıları ve zaman ortalamalı akış özellikleri incelenmiştir. Ölçümler açığa çıkarmıştır ki delikli yüzeylerde genişlik oranı Y/D=1.0 olan silindirler etkili olmaktadırlar. Ayrıca yakın dalga bölgelerinde 1.5D mesafesine kadar olan yerlerde girdap oluşumu gözle görülür şekilde bastırılmaktadır. Hız profilleri ve akış yapılarının değişik delikli yüzeylerde etkilendikleri ve sonuç olarak koherent yapıların yok olduğu tesbit edimliştir. Ek olarak eğimli iki düz plakanın etkileşimi deneysel olarak incelenmiştir. İki plakanın arasındaki boşluk oranının ( g/D ) atak açısı (α ) ile birlikte dalga bölgelerindeki akış yapıları, koherent ve incoherent zaman ortalamalı özellikleri incelenmiştir. Değişik deney setleri için boşluk oranları 0.5 ve 1.5 arasında olan plakalar yapılmış, tek ve çift gövdeli girdap modları gözlemlenmiştir. Ayrıca atak açısı 45-75 dereceler arasında çalışılmış ve meyilin dalga bölgesinde girdap frekansı ve Strouhal numarasının değişimi araştırılmıştır. Neticeler göstermiştir ki atak açısı arttıkça Strouhal sayısı düşmektedir. Ayrıca boşluk oranının artması ile akış yapılarının etkilendiği ve turbulent kinetic enerjisi üretiminin akış arkasında ilerledikçe azaldığı gözlemlenmiştir. Anahtar kelimeler: Girdap, Bastırma, İnkoherent ve koherent akış yapısı, Delikli kare silindir, Meyilli düz plaka, ardışık düzenleme.
Doctor of Philosophy in Mechanical Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2016. Supervisor: Assoc. Prof. Dr. Hasan Hacışevki
Keywords: Mechanical Engineering; Bluff Bodies-Vortex; Vortex Shedding; Suppression; incoherent and coherent flow structure; Perforated Square Cylinder; Inclined flat plate; Interacting wake; Tandem arrangement